Peran Teknologi Pembelajaran Terhadap Motivasi Belajar Siswa Dalam Pendidikan MIPA - Irfan Shaifuddin M (International Forum of Researchers and Lecturers, 2023)
Technology has changed the educational landscape by providing greater access to learning resources, creating interactive and engaging learning environments, and supporting the use of virtual simulations and experiments. Customisation of learning and the ability to track student progress through technology is an important focus in the effort to improve student learning motivation in Mathematics and Natural Sciences Education. This research uses qualitative research methods with literature study data collection techniques to investigate the impact of using learning technology on student learning motivation in Mathematics and Natural Sciences Education. The purpose of this research is to provide a deeper understanding of how learning technology can be optimised to improve student learning motivation in Mathematics and Natural Sciences. The results of this study have the potential to provide relevant recommendations that can help improve Mathematics and Natural Sciences education in the current digital era. This research is expected to make a significant contribution to the understanding of how learning technology can be used more effectively in increasing student learning motivation in Mathematics and Natural Sciences, so that it can provide maximum benefits in preparing students to face global challenges in the future.